Security Externalities of the Chinese Maritime Silk Road Initiative in the Indian Ocean, with Focus on Sino-Indian Competition - Burešová, Hana; Garlick, Jeremy; Havlová, Radka, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The goal of this thesis is to provide a clearer understanding of the consequences – here especially security externalities – of the development along the Chinese Maritime Silk Road in the Indian Ocean. There are two aspects of this issue, firstly how Maritime Silk Road Initiative affects small economies perceived by China as strategic, and secondly the threats and opportunities of the Maritime Silk Road and String of Pearls in the waters of Indian Ocean.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses